The Influence of Different Drying Methods on Constituents and Antioxidant Activity of Saffron from China. (30th March 2015) - Tong, Yingpeng; Zhu, Xingyi; Yan, Yongqiu; Liu, Ruoxi; Gong, Feng; Zhang, Ling; Hu, Jiangning; Fang, Ling; Wang, Ruwei; Wang, Ping
Abstract : More and more saffron has been cultivated in China because of the increasing saffron demand, but no paper has studied the influence of drying methods on the quality of Chinese saffron. In this paper, three different dehydration treatments applied in actual production were evaluated: dehydration with electric oven, vacuum oven, and microwave. We determined that the highest quality of saffron will be obtained when fresh saffron is treated at higher temperatures (no more than 70°C) for a long time by electric oven drying and vacuum oven drying. In microwave drying, treatments at lower microwave power and longer time benefit the quality of saffron. In addition, the influence of the drying method on antioxidants in saffron is discussed. The correlation between individual saffron profiles and the antioxidant value was estimated by spectrum-effect relationships analysis.